Development And Characterization Of Lovastatin Controlled Release Buccoadhesive Dosage Form - DOIJAD R.C; SOMPUR C.K; GOJE A.J; MASKE A.P; TAMBOLI F.A (International Journal of Pharma and Bio Sciences, 2011)
Recent years have seen an increasing interest in development of Novel mucoadhesive buccal dosage form. These are useful for the systemic delivery of drug as well as for local targeting of drug to particular region of body. Buccoadhesive tablets were prepared by direct compression method by using various mucoadhesive polymers namely Carbapol 934P, PVP K30, HPMC K4M, HPMC K100M, Colour Tartarazine and Sodium Saccharin. Prepared